Peningkatan Hasil Belajar Pendidikan Kewarganegaraan Melalui model Pembelajaran Snowball Throwing Pada Murid Seolah Dasar Negeri 3 Jagon Kecamatan Pangkajene Kabupaten Pangkep - Arahim S (Universitas of Muhammadiyah Makassar, 2018)
The purpose of this study is to improve the learning outcomes of Citizenship Education through the model of learning Snowball Throwing on the fourth grade of elementary school students 3 District jagong district Pangkep. This research is a classroom action research conducted two cycles, each cycle. The test of the learning result can be analyzed quantitatively and the result of the observation sheet is analyzed qualitatively. The results showed that in the first cycle the average value of learning outcomes of Civics Education 65.6 students and are in the medium category with the completeness category of 11 unfinished students and 15 completed students with Minimum Exhaustiveness Criteria. In Cycle II the average value of learning outcomes Civics Education 78.27 is in the high category with the completeness category of 26 complete students. Completeness of student learning outcomes increased after the implementation at the State Elementary School 3 Jagong Pangkajene District Pangkep District that is in the first cycle there are 11 students who have not completed and in Cycle II all the students to be thorough. Based on the results of the above study, it can be concluded that the learning model of Snowball Throwing can improve the outcomes of Citizenship Education on Pupils of Class IV State Elementary School 3 Jagong Pangkajene District Pangkep District.Keywords: Learning Outcomes, Snowball Throwing Learning Model